Surgical palliation in poorly differentiated neuroendocrine carcinoma of the hypopharynx: Case report. Issue 8 (5th October 2021) - Fiorini, Francesca Romana; Abbas, Yasmin; Mukhopadhyay, Suchana; Tatla, Taran
Abstract: Background: Primary neuroendocrine carcinomas (NECs) are very rare entities accounting for 0.49% of all malignancies. Within the head and neck, the most common sites are the larynx and paranasal sinuses, while the hypopharynx is seldom described. Case: We present a patient with a poorly differentiated metastatic NEC of the hypopharynx treated palliatively with organ‐preserving surgery and post‐operative chemotherapy, and literature review for well‐documented pure hypopharyngeal NECs. Our patient died of chest infection during chemotherapy, 4 months after surgery. Conclusion: Chemotherapy remains the mainstay of treatment in the presence of metastases with 2‐year overall survival of 15.7%. Due to the aggressive nature of poorly differentiated metastatic NECs, surgical management is seldom considered. We report and advocate the successful palliative role of organ‐preserving, minimally invasive trans‐oral LASER micro‐surgery and neck dissection to control loco‐regional head and neck disease, safe‐guarding better quality of home life, despite limited life expectancy for this condition.